Diffusion approximation of statistical experiments with persistent linear regression and equilibrium - Koroliouk, D.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
We propose an approximation of statistical experiments with persistent linear regression and equilibrium by Markov processes in the discrete-continuous time: k=[Nt], 0≤t≤T, for which the diffusion approximation of an Ornstein–Uhlenbeck-type process with continuous time is constructed.